Atributos químicos de um argissolo irrigado com efluente de laticínios diluído no semiárido potiguar - Mendes, Hérick Claudino (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this work was to analyze the changes in the chemical attributes of an ultisol irrigated with different dairy effluent dilutions. The experiment was set up using a randomized block design with five dilutions of dairy effluent (DE) in public water supply (PWS) (T1 - only PWS, T2 - 10% of DE plus PWS, T3 - 20% of DE plus PWS, T4 - 30% of DE plus PWS, and T5 - 40% of DE plus PWS). This work was carried out from April 18 to December 18, 2015. Soil samples were collected at five depths to quantify the attributes of pH, organic matter (OM), potassium (K), phosphorus (P) and electrical conductivity of the soil saturation extract (ECss). No significant effects of dairy effluent dilutions were found in altering the pH, OM and K+ values of the ultisol after 240 days of application. However, there was a significant increase of P in T4, and of ECss mainly in the 0.10 to 0.20 m layer of T5.
Monografia
Keywords: Reúso; Água residuária industrial; Qualidade do solo; Reuse; Industrial wastewater; Soil quality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA